Conclusive evidence for a population of water worlds around M dwarfs remains elusive - Rogers,JGG; Schlichting,HEE; Owen,JEE (Letters of the Astrophysical Journal, 2023)
The population of small, close-in exoplanets is bifurcated into super-Earths and sub-Neptunes. We calculate physically motivated mass–radius relations for sub-Neptunes, with rocky cores and H/He-dominated atmospheres, accounting for their thermal evolution, irradiation, and mass loss. For planets 10 M⊕, we find that sub-Neptunes retain atmospheric mass fractions that scale with planet mass and show that the resulting mass–radius relations are degenerate with results for "water worlds" consisting of a 1:1 silicate-to-ice composition ratio. We further demonstrate that our derived mass–radius relation is in excellent agreement with the observed exoplanet population orbiting M dwarfs and that planet mass and radii alone are insufficient to determine the composition of some sub-Neptunes. Finally, we highlight that current exoplanet demographics show an increase in the ratio of super-Earths to sub-Neptunes with both stellar mass (and therefore luminosity) and age, which are both indicative of thermally driven atmospheric escape processes. Therefore, such processes should not be ignored when making compositional inferences in the mass–radius diagram.